Tick-Borne Infections Incidence among the Population of Siberian and Far East Federal Districts in 2009 and 2010 and Prognosis for 2011 - A. Ya. Nikitin; E. A. Sidorova; E. I. Andaev; M. V. Chesnokova (Проблемы особо опасных инфекций, 2011)
Presented are the data on tick-borne infections (tick-borne encephalitis, tick-borne borrelioses and rickettsioses) incidence among the population of the constituent entities of Siberian and Far East Federal Districts in 2009 and 2010. Given is the prognosis on tick-borne encephalitis and tick-borne borrelioses incidence among the population of the Districts for 2011. Generalized information on the amount of preventive measures is presented and the ways of their improvement are discussed.